2006
DOI: 10.1016/j.rmed.2005.06.015
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of airflow obstruction in rural primary care

Abstract: The objective of this study was to determine the prevalence and severity of airflow obstruction in rural primary care settings and the degree to which it can be predicted by clinical characteristics. Spirometry was performed in patients 35 years and older who had smoked, presenting for any reason to one of eight rural primary care practices. Obstruction was defined as an FEV(1)/FVC<0.70. A total of 1046 subjects were recruited of whom 1034 had acceptable and reproducible spirometry. Airflow obstruction was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…This prevalence rate among male cigarette smokers is lower than what has been reported in developed countries, including Spain (12.1%),18 Canada (13.1%),19 Sweden (14%),20 and the United States (16%) 21. This can be explained by the fact that our population is generally younger, with more than two thirds of our subjects younger than 60 years.…”
Section: Discussioncontrasting
confidence: 73%
“…This prevalence rate among male cigarette smokers is lower than what has been reported in developed countries, including Spain (12.1%),18 Canada (13.1%),19 Sweden (14%),20 and the United States (16%) 21. This can be explained by the fact that our population is generally younger, with more than two thirds of our subjects younger than 60 years.…”
Section: Discussioncontrasting
confidence: 73%
“…We observed a 50% prevalence of unrecognized OLD, higher than that observed in rural, medical inpatient, and Spanish community-based populations 7,9,36. Based on our findings, prevalence estimates of disease burden from OLD are likely to be significantly underestimated in the urban IDU population.…”
Section: Discussionmentioning
confidence: 40%
“…OLD is frequently unrecognized even in smokers 46. Several studies have identified populations at higher risk for unrecognized OLD including rural populations,7 the urban homeless,8 and medical inpatients 9,10. Urban populations with a history of current or former drug use represent a poorly studied group with a substantial burden of tobacco abuse and lower socioeconomic status 11–13.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate knowledge of COPD prevalence in primary care has been considered critical to planning strategies for detection and management of the disease. COPD prevalence in this setting has been analysed elsewhere . Using a similar design to the present study (opportunistic case finding), Hill et al .…”
Section: Discussionmentioning
confidence: 95%
“…Cough was the most common symptom (53.7%). In rural primary care settings, Dales et al . determined COPD prevalence in smokers (≥35 years) presenting for any reason.…”
Section: Discussionmentioning
confidence: 99%